Evaluation of the application of Slovenia to be recognised as having a negligible risk of classical scrapie - European Food Safety Authority (EFSA); Giulio Di Piazza; Giuseppe Ru; Marion Simmons; Barbara Lanfranchi; Angel Ortiz‐Peláez (EFSA Journal)
Abstract Slovenia submitted a request to the European Commission to be recognised as a Member State with negligible risk of classical scrapie. EFSA has been asked to assess if Slovenia has demonstrated that, between 2016 and 2022, a sufficient number of ovine and caprine animals over 18 months old, representative of those slaughtered, culled or found dead have been tested, and will continue to be tested annually, to provide a 95% confidence of detecting classical scrapie if it is present at a prevalence rate exceeding 0.1%. A risk‐based approach using stochastic scenario tree modelling accounting for surveillance stream and species was applied. Globally, there is still a lack of data on the performance of the approved diagnostic screening tests under field conditions, specifically for sheep. Therefore, alternative scenarios were explored extending the range from the sensitivity (99.6%) provided by the past European Union evaluations to a sensitivity of 50%, more consistent with published data obtained under field conditions in infected goat populations. It was concluded that during the period 2016–2023, Slovenia has tested annually a sufficient number of ovine and caprine animals over 18 months of age, sourced from the NSHC and SHC populations, to ensure a 95% level of confidence of detecting CS if it is present in that population at a prevalence rate exceeding 0.1%, assuming a test sensitivity of 90% or above. The same holds for the years 2016, 2021 and 2023, assuming a test sensitivity of at least 80%. Based on the proposed number of samples for 2024 and future years, Slovenia would continue to meet the testing requirements assuming a test sensitivity of at least 80%.